Pengembangan Media Pembelajaran Buku Berbasis Scrapbook pada Materi IPA - Bela Ernadayanti (Tarbiatuna: Journal of Islamic Education Studies, 2024)
The development of books as media or reading materials for now is still very little made. One of the development of books as a learning medium or reading material today is by making scrapbook-based books. The type of research conducted by researchers uses the Sukmadinata development research model. The R&D cycle refers to Sukmadinata (2007: 184) can be simplified into three main steps, where each step includes several operational steps. The scrapbook-based book learning media developed has gone through a validation process. The results of the media expert validation test obtained a score of 95.2%, said to be very valid and can be used by grade VI students. The results of the material expert test obtained a score of 96.0%, very valid and can be used by students. The percentage results state that scrapbook-based book learning media products are very valid in terms of the material listed in them already meet the criteria. Pretest scores are obtained from before students get lessons using scrapbook learning media. While posttest scores are obtained after students get lessons using scrapbook learning media. The average pretest score obtained by students was 62.6 and the posttest score obtained by students was 86.1 in grade VI students of SD Negeri Kaliwunggu 01 totaling 16 students. After measuring the level of initial understanding and the level of final understanding, students test the difference in the average value of initial understanding and final understanding with the N-Gain Score test which is calculated using SPSS. The result of calculating the N-gain score using SPSS gets a result of 0.62. These results show that scrapbook-based learning media get a medium category in terms of effectiveness. Judging from the results of N-Gain measurements in the form of percent, obtaining a result of 62.6% is said to be quite effective. Judging from the results of the N-Gain Score calculation, there are differences in the level of understanding of students before and after using scrapbook learning media in the learning process. So, scrapbook-based book learning media is effective in increasing the understanding of grade VI students on science material.